Corporate Shares as Shares - Katz, Larissa (Modern Studies in Property Law, 2019)
In this chapter, I ask whether shares in corporations ought to command more attention within theories of property. Contemporary liberal property theorists typically take land (and sometimes goods) as the basic case of property. Shares tend to be left out of these accounts or treated as imitations or mutations of the basic case. Economists, for their part, have transformed the idea of ownership: ‘owner’ refers to the ultimate beneficiary of the value of assets. Shares are treated as a central case of property by those who take this approach. Shareholders are taken to own the corporation insofar as they are the ultimate beneficiaries of its value. In this chapter, I concede shares do not fit within the traditional property framework. This does not mean, however, that the traditional idea of property is obsolete and that a new property framework is in order.

Women in private international law - Keyes, Mary E. (Research Handbook on Feminist Engagement with International Law, 2019)
There has been almost no consideration of the position of women in private international law. There is very little published research applying a feminist analysis to, or even considering the position of women in, private international law. This field gives almost no attention to the particular interests, positions and experiences of women as subjects of the law, or the contribution of women as makers of the law. In the common law, private international law was largely developed in the 19th century, by male judges who were strongly influenced by commentary written exclusively by men. This chapter establishes that the apparently gender-neutral nature of private international law conceals profoundly ingrained assumptions about gender, in which the masculine is represented as a rational and sophisticated businessman, and the feminine is represented as a legally incapable wife. It then considers the gendered dimension of private international law in international family law, referring in particular to the regulation of international child abduction, international family property agreements, and international commercial surrogacy. Each of these examples demonstrates the differential impact of the law on women, indicating the need for greater awareness of and attention to gender. It concludes that while there have been some advances recently, particularly in terms of increased representation of women in making and commenting on private international law, there remains a great need for further research into the position of women as legal subjects and law-makers in this field.
Keywords: Private International Law; Woman

Arbitrage commercial international - Besson, Sebastien (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

L'avocat et la médiation - entrez dans la danse ! - Lévy, Cinthia (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)

El contenido del acuerdo social de ejercicio de la acción social de reponsabilidad. Especial referencia al ámbito subjetivo - Moreno Buendía, Francisco Jesús (Estudios sobre la responsabilidad de los administradores de las sociedades de capital a la luz de sus recientes reformas legislativas y pronunciamientos judiciales, 2018)

Le Droit minier camerounais - Nyoth Hiol, Michel (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
À l’image de certains pays d’Afrique noire, le secteur minier est devenu au Cameroun, le cadre d’une activité économique majeure. À l’origine de ce ‘boom minier’, la richesse du sous-sol. En effet, le pays regorge de gisements miniers d’importance mondiale.¹ On y dénombre une grande variété allant du manganèse, du diamant, de l’or, au cobalt etc.² Ajoutée à cette carte minière attrayante, des réformes entreprises par le législateur minier et soutenues par des donateurs, en l’occurrence les institutions de Bretton Woods au secours des économies sinistrées. En effet, pour relancer l’activité économique sinistrée dans les années 90, le sous-sol se

International Trade, Environment and Sustainable Development - Ruppel, Oliver C. (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Issues related to international trade and the environment undoubtedly are of significance to developing countries like Cameroon because they argue that developed countries have depleted resources and indulged in environmentally harmful practices during the past century, in order to achieve unprecedented high standards of living.² The developing countries therefore demand a general but differentiated responsibility, seeking open trade and compensation for adopting environmentally restraining policies.³ Upon further reflection on the link between economic growth activities, environmental protection and social development, the triangular debate on these topics will be highlighted briefly, by introducing the various perspectives.⁴ Trade creates the wealth, which

Droit et politique du commerce au Cameroun et protection de l’environnement - Songue, Emma Marie Solange NGONDJE (Environmental law and policy in Cameroon - Towards making Africa the tree of life | Droit et politique de l'environnement au Cameroun - Afin de faire de l'Afrique l'arbre de vie, 2018)
Le droit commercial au Cameroun est régi par l’Acte uniforme révisé de l’Organisation pour l’harmonisation en Afrique du droit des affaires (OHADA) portant droit commercial général¹ en son article 1 qui renvoie, aux lois non contraires à l’Acte iniforme applicables dans l’État partie où se situe l’établissement ou le siège social du commerçant ou de l’entreprenant. Ce droit dont la finalité pour les principaux acteurs que sont les commerçants est la recherche du profit et pour l’État le développement économique ne saurait ignorer d’autres finalités importantes pour tous. Il s’agit des questions environnementales dont les nombreuses messes démontrent l’urgence de

Médiation et arbitrage dans les services financiers : conseil en placement et gestion de fortune - Thévenoz, Luc (Arbitrage, médiation et autres modes pour résoudre les conflits autrement, 2018)
Dans le contexte actuel d'échange automatique de renseignements en matière fiscale, quelles sont les perspectives de la médiation et de l'arbitrage comme modes de résolution des litiges relatifs aux services financiers - spécialement la gestion de fortune et le conseil en placement - que la place financière suisse offre à sa clientèle privée et institutionnelle suisse et étrangère? Cet article commence par un rapide tour d'horizon international de la situation. Il examine ensuite le développement de la médiation qui résultera de la mise en oeuvre de la loi sur les services financiers et s'achève par quelques réflexions sur l'arbitrage et les actions collectives dans ce domaine.
Keywords: Conseil en placement; Gestion de fortune; Médiation; Services financiers

El poder de decisión en las sociedades en situación de insolvencia y de déficit patrimonial la incidencia de los expedientes preconcursales - Vázquez Cueto, José Carlos (Sociedades y concurso, 2018)

Responsabilidad de administradores por daños en el ámbito de la llevanza de la página web de las sociedades de capital no cotizadas - Vázquez Cueto, José Carlos (Derecho Mercantil y Tecnología, 2018)
Este trabajo trata del régimen especial de responsabilidad de los administradores por la llevanza de las páginas web corporativas de las sociedades de capital no cotizadas, establecido por el art.11-ter LSC. Este régimen, que solo se aplica al deber de mantenimiento de lo insertado y a la garantía de ausencia de interrupción al acceso, descarga e impresión gratuitos de la información publicada, parece diferir del régimen general de responsabilidad de administradores, establecido en los arts.236 a 241-bis, en algunos aspectos. El autor analiza esas diferencias, que pueden constituir la causa del pobre empleo en la actualidad de este instrumento en las sociedades de capital españolas.
Keywords: Capital companies’ website; Directors’ liability; Non-listed capital companies; Página web corporativa; Responsabilidad de administradores; Sociedades de capital no cotizadas

Disqualification Decisions under the ICSID Convention and Arbitration Rules - Cleis, Maria Nicole (The Independence and Impartiality of ICSID Arbitrators, 2017)
This Chapter aims to distill a consistent approach to arbitrators’ independence and impartiality from past decisions on disqualification requests. In a first part, the interpretation of the manifest lack requirement provided for in Article 57 icsid Convention is scrutinized. The definition of this threshold (i.e. the burden of proof imposed on the challenging party) is crucial, because it determines the effectiveness of the right to an independent and impartial decision-maker. The second part of the Chapter inquires how specific categories of alleged conflict are dealt with. It seeks to derive consistency and predictability from the outcome or reasoning of disqualification

Las operaciones de transporte aéreo comercial realizadas por empresas sin licencia de explotación - Navarro Peral, Manuela (El derecho aéreo entre lo público y lo privado: aeropuertos, acceso al mercado, drones y responsabilidad, 2017)
El presente trabajo constituye un breve análisis jurídico de una práctica atípica que ha venido desarrollándose en España durante los últimos años tomando como ejemplo el caso Hispania Airways, una sociedad mercantil dedicada al transporte de pasajeros, correo y carga que inició sus operaciones sin obtener la correspondiente licencia de explotación. Se abordan las posibles causas de la permisividad de este tipo de operaciones por parte de la autoridad aeronáutica.
Keywords: Contratos de utilización de aeronaves; Control administrativo; Infracciones; Ley de Seguridad Aérea; Licencia de explotación; Obligaciones; Sujetos; Transporte aéreo

Institutional and Contextual Factors Effects on Entrepreneurship in Cameroon: The Case of the Transport Sector - Okah-Efogo, Françoise; Okah-Atenga, Crescence Marie-France (Entrepreneurship in Africa, 2017)
In Africa, whatever the considered age group, there are more entrepreneurs in the early stages of entrepreneurship than anywhere else in the world (Global Entrepreneurship Monitor (GEM) Report 2014). According to the gem survey (2014), 55.57 per cent of the population between 18–64 years expresses entrepreneurial intentions in Cameroon. Similarly, 37.4 per cent of the same age population is in the early course of their business activity. Between 2014 and 2015, total entrepreneurial activity has decreased in Cameroon (from 37.4 per cent to 25.4 per cent of all adults). Nonetheless, 61.1 per cent of the respondents think that entrepreneurship

La noción de accidente en la determinación de la responsabilidad del transportista en el contrato de pasaje aéreo por daños personales - Rojo Álvarez-Manzaneda, Rafael (El derecho aéreo entre lo público y lo privado: aeropuertos, acceso al mercado, drones y responsabilidad, 2017)
En el marco del contrato de transporte aéreo de pasajeros, la determinación de los presupuestos que hacen nacer la responsabilidad de las compañías áreas en caso de accidente, sigue planteando, a tenor de lo dispuesto en su normativa especial, serias dudas interpretativas tanto en la jurisprudencia como entre nuestra doctrina. Entre ellas, precisamente, está la propia noción de lo que debe, a estos efectos, entenderse por “accidente”, habida cuenta de que la normativa no nos ofrece una definición expresa al respecto. Aún identificando el accidente como la causa última del daño, y no con el daño en sí, no todo hecho que termine provocando la muerte o las lesiones en un pasajero debe merecer aquella calificación. La noción de accidente engloba aquellos sucesos que, directamente relacionados con las operaciones y la utilización de la propia aeronave como medio de transporte, provoquen un daño. La identificación, en este sentido, con los accidentes aéreos es indudable. Las dudas, sin embargo, se centran en aquellos otros sucesos que, ante un desenvolvimiento normal del vuelo en sí, puedan provocar un daño al pasajero. Pues no cabe duda de que la legislación especial también hace responsable a las compañías aéreas de los accidentes que tengan lugar, no sólo a bordo de la aeronave, sino en las operaciones de embarque y desembarque.
Keywords: Accidentes aéreos; Pasajeros; Transporte aéreo

Les pratiques coopératives au Mali : irrespect de la règle de droit ou construction d'un droit vivant ? - Hiez, David (l'Effectivité du droit économique dans l'espace OHADA, 2016)
Keywords: Coopérative; Doit aficain; OHADA; coopératives africaines; éffectivité

L'effectivité du droit économique dans l'espace OHADA - Hiez, David; Menétrey, Séverine (l'Effectivité du droit économique dans l'espace OHADA, 2016)
Keywords: Droit africain; Droit coopératif; Effectivité; OHADA

Les contrats relatifs au savoir-faire et autres secrets d’affaire - Vanbrabant, Bernard (Les contrats commerciaux en pratique, 2016)

L’arbitrage en matière d’assurance maritime - Zerhouni, Farouk (Le droit maritime dans tous ses états : Hommage méditerranéen à Pierre Bonassies, Philippe Delebecque et Christian Scapel, 2016)

El ejercicio anticipado de la acción cambiaria por resultado infructuoso del embargo de bienes del librado en la ley cambiaria y en el proyecto de código mercantil - Baena Baena, Pedro Jesús (Estudios sobre el futuro Código Mercantil: libro homenaje al profesor Rafael Illescas Ortiz, 2015)
La ausencia de toda referencia en el Proyecto de Código Mercantil a la especialidad contenida en la vigente Ley cambiaria, por la que se permite al tenedor de la letra de cambio el ejercicio de la acción de regreso antes del vencimiento del título en caso de resultado infructuoso del embargo de bienes del librado, lleva a plantearnos la razón de ser de esta posibilidad y la conveniencia o no de su inclusión en el Código proyectado. La exposición del tema nos conduce colateralmente a reflexionar sobre el ejercicio anticipado de la acción directa y sobre si en el caso de embargo infructuoso de los bienes del librado resulta necesario el protesto para el ejercicio de la acción cambiaria de regreso, tanto a la vista de la vigente Ley cambiaria como a la del Código Mercantil propuesto.

Regional Integration in Africa through the Harmonisation of Laws - Simo, Regis Yann (Regional Integration and Policy Challenges in Sub-Saharan Africa, 2014)
Domestic laws on the African continent have been considered inadequate to attract the investment needed for development and economic growth. A crucial catalyst in attracting investment on the continent is law reform. The formulation of legislation has twofold effects: firstly, it is perceived to mitigate the risks associated with doing business in Africa; secondly, it legally obligates African governments to comply with standards of protection accorded to international investors through the regulation of the business environment. The formulation of legislation is a key determinant of the quality of investment attracted to the continent. This Chapter assesses how the Organization for the Harmonization of African Business Law (OHADA) has contributed to regional integration and economic growth on the continent.
Keywords: Africa; Institutions; Law Reform; OHADA; Regional integration

Legal Innovation for Development: The OHADA Experience - Frilet, Marc (Legal Innovation and Empowerment for Development, 2013)
The World Bank legal review gathers this input from around the world and compiles it into a useful resource for all development practitioners and scholars. The subtitle of this volume, legal innovation and empowerment for development, highlights how the law can respond to the chal-lenges posed to development objectives in a world slowly emerging from an economic crisis. The focus on innovation is a call for new, imaginative strategies and ways of thinking about what the law can do in the development realm. The focus on empowerment is a deliberate attempt to place the law into the hands of the poor; to give them another tool with which to resist poverty. This volume shows some of the ways that the law can make an innovative and empowering difference in development scenarios. Development problems are complex and varied, and the theme of innovation and empowerment naturally has a broad scope. Consequently, this volume reaches far and wide. It considers the nature, promise, and limitations of legal innovation and legal empowerment. It looks at concrete examples in places such as Africa, the Asia-Pacific region, and Latin America. It considers developments in issues with universal application, such as the rights of the disabled and the effectiveness of asset recovery measures. The theme of legal innovation and empowerment for development complements substantive and institutional sensibilities in current development policy. Substantively, development policy discourse seems to have moved away from tacking hard toward statist policy or neoliberal policy. Although this brief introduction cannot do justice to the richness and complexity of these contributions, it does consider each focal point in turn.

The State of IFRS in Africa: Is IFRS in Disarray? - Zori, Solomon George (Governance across borders transnational fields and transversal themes, 2013)

Le droit congolais des sociétés et la perspective OHADA - De Wolf, Patrick (Le droit de l'OHADA : son insertion en République Démocratique du Congo, 2012)

Las fuentes del derecho marítimo - Jiménez Sánchez, Guillermo Jesús (Estudios de derecho marítimo, 2012)

La preuve en droit commercial - Mougenot, Dominique (Vade-mecum du juge consulaire, 2012)

Chapitre II. Le consentement à l’arbitrage, manifestation d’une volonté contenue - Diallo, Ousmane (Le consentement des parties à l'arbitrage international, 2010)

Chapter 42, Dissenting Opinions by Party-Appointed Arbitrators in Investment Arbitration - van den Berg, Albert Jan (Looking to the future: essays in international law in honor of W. Michael Reisman, 2010)
Dissenting opinions appear to have become an accepted practice in international arbitration. Th e current debate concentrates on their procedure, form, and content. Alan Redfern noted that “[a]t present, a generally relaxed attitude towards dissenting opinions seems to be taken not only by the arbitral institutions, but also by the arbitrators themselves … .” In this contribution, I would like to explore the cautionary note with which Redfern concluded his seminal article, namely, that the “[t]ime has perhaps come to inquire whether the present leniency towards dissenting opinions … has gone too far.” I propose to do so with respect to investment arbitrations because ade available publicly, particularly party-appointed arbitrators’ dissenting opinions.
Keywords: Arbitrage; Arbitration; Arbitrator; Dissenting opinion; Investment arbitration; Opinion dissidente